Increase in tumour-infiltrating lymphocytes with regulatory T cell immunophenotypes and reduced zeta-chain expression in nasopharyngeal carcinoma patients. - Seow, Heng Fong; Abdullah, Maizaton Atmadini; Yip, Wai Kien; Yusoff, S. M. (Wiley-Blackwell, 2009)
The pathological significance of the mechanisms of tumour immune-evasion and/or immunosuppression, such as loss of T cell signalling and increase in regulatory T cells (Tregs), has not been well established in the nasopharyngeal carcinoma (NPC) microenvironment. To evaluate the Treg immunophenotypes in tumour-infiltrating lymphocytes (TILs), we performed a double-enzymatic immunostaining for detection of forkhead box P3 (FoxP3) and other markers including CD4, CD8, and CD25 on 64 NPC and 36 non-malignant nasopharyngeal (NP) paraffin-embedded tissues. Expression of CD3ζ and CD3ε was also determined. The prevalence of CD4+FoxP3+ cells in CD4+ T cells and the ratio of FoxP3+/CD8+ were increased significantly in NPC compared with those in NP tissues (P < 0·001 and P = 0·025 respectively). Moreover, the ratio of FoxP3+/CD25+FoxP3− in NPC was significantly lower than that in NP tissues (P = 0·005), suggesting an imbalance favouring activated phenotype of T cells in NPC. A significant negative correlation between the abundance of FoxP3+ and CD25+FoxP3− cells (P < 0·001) was also identified. When histological types of NPC were considered, a lower ratio of FoxP3+/CD25+FoxP3− was found in non-keratinizing and undifferentiated carcinomas. Increased CD4+FoxP3+/CD4+ proportion and FoxP3+/CD8+ ratio were associated with keratinizing squamous cell carcinoma. A reduced expression of CD3ζ in TILs was found in 20·6% of the NPC tissues but none of the NP tissues. These data provide evidence for the imbalances of Treg and effector T cell phenotypes and down-regulation of signal-transducing molecules in TILs, supporting their role in suppression of immune response and immune evasion of NPC.